The relationship between diversity and productivity from a three-dimensional space view in a natural mesotrophic lake - Ai-Ping Wu (Elsevier, 2021)
The relationship between diversity and productivity (DPR) is a hot topic in ecology, whereas most evidence comes from studies of manipulated terrestrial ecosystems or from two-dimensional space views. In this study, we determined DPR of submerged plants in a natural mesotrophic lake, Lake Erhai, along its water depth in 2013 and 2019. Our results demonstrated that the community productivity was significantly negatively correlated with plant biodiversity from a three-dimensional space view (all of the water depths) in Lake Erhai due to strong competition effects among submerged species. However, DPR patterns at each water depth (from two-dimensional space views) were various, which might be because these DPR patterns were disturbed by many biotic and abiotic factors or their interplays. Both total biomass and biomass of dominant species negatively correlated with species richness. Moreover, total biomass was positively correlated with biomasses of dominant species. Accordingly, we can presume that DPR patterns are largely determined by relationships between biomasses of dominant species and biodiversity in our study. Our results showed that species number in 2019 was generally smaller than that in 2013 and submerged species were migrating from deep water to shallow water with lake eutrophication in such a short time. Accordingly, measurements should be conducted quickly to control the eutrophication process of Lake Erhai to improve its multiple valuable functions and services.